Interaction between κ- and ι-carrageenan and anthocyanins from Vaccinium myrtillus. (5th September 2016) - Navikaite, Vesta; Simanaviciute, Deimante; Klimaviciute, Rima; Jakstas, Valdas; Ivanauskas, Liudas
Highlights: Formation of complexes between κ- or ι-carrageenan (CARG) and anthocyanins (ATCs). Study of ATCs equilibrium adsorption on cross-linked CARG. Purification of ATCs during adsorption on cross-linked CARG. Incorporation of ATCs on CARG confirmed by FT-IR and HPLC. Abstract: Anthocyanins (ATCs) from the Vaccinium myrtillus water extract have been incorporated into the κ-carrageenan (κ-CARG) or ι-carrageenan (ι-CARG) during complexation in dilute solutions or adsorption onto the microgranules of κ-CARG or ι-CARG cross-linked with epichlorohydrin. At the optimal weight ratio of CARG to ATC at 0.4:1 and the total ATCs and CARG concentration ≤ 0.07 g/L, stable dispersions of the κ-CARG/ATCs or ι-CARG/ATCs complex nanosize particles were obtained. The Langmuir, Freundlich and Dubinin-Radushkevich adsorption models have been used to describe the equilibrium adsorption of ATCs on cross-linked CARG. The introduction of ATCs into CARG and cross-linked CARG was confirmed by FT-IR spectroscopy. The data of the HPLC analysis showed that during adsorption on cross-linked ι-CARG microgranules ATCs are isolated from the crude water extract of wild bilberries, whereas other phenolics remain in the adsorption solution. After desorption from cross-linked CARG/ATC into different media the sufficiently pure and stable solutions of ATCs were obtained.